Polyandry and genetic diversity in populations of Pholidoptera griseoaptera along an environmental gradient - Jutzeler, Matilda (2019)
Polyandry is a common mating pattern in different insect species and it leads to increased genetic diversity in the offspring and prevents inbreeding in populations. According to the theory of mate choice, mates should choose a partner that will increase heterozygosity in their offspring. In this way females will increase their reproductive success and offspring will have higher fitness and be good competitors. Phenotypic traits such as large body size is preferred by both females and males crickets according to earlier studies. The environment can also have an influence on mating pattern as sexual selection could vary depending on the environment. I used the dark bush-cricket, Pholidop-tera griseoaptera in an experiment to examine the mechanisms behind polyandry and the correlation between phenotypic, genetic and environmental factors. My general aim was to broaden the knowledge about the mating system in this insect species. The study was placed at Slovak Academy of sciences in Slovakia. Bush-crickets from five different altitudes were collected, and mating experiments was performed using the offspring of these animals. Eleven mating groups were used with 5 females and 5 males in each group. The bush-crickets were kept in either warm or cold temperatures in open-air cages. Microsatellites was used to identify genetic diversity of populations to examine if there was a correlation with the frequency of copulations. Measurement of body-size were performed on each cricket and estimation of number of copulations were done for each female.I found that in warm temperature, females of P. grisoptera had the highest frequency of copulations and there males choose high quality females. In cold temperature there were less copulations, indicating that the environmental condition restrict the ability for mate choice. This study is only a snapshot of the pattern of polyandry and the behaviour needs to be studied further, but it has broadened the knowledge about the mating system in this nuptial gift-giving insect species.